ULASAN BUKU (EXTENDED): "ISLAM AND LITERALISM: LITERAL MEANING AND INTERPRETATION IN ISLAMIC LEGAL THEORY": Book Review (Extended): "Islam and Literalism: Literal Meaning and Interpretation in Islamic Legal Theory" - Buang, Ahmad Hidayat (Jurnal Syariah, 2018)
Book Review (Extended): "Islam and Literalism: Literal Meaning and Interpretation in Islamic Legal Theory"